The Lawyer's Guide to Strategic Practice Management : 2nd edition /: 2nd edition. (2015) - Williams, Viv; Ertel, Danny; Horowitz, Lisa B; Greene, Arthur G; Wheatley Burt, Patricia; Trueheart, Harry P; Lamb, Patrick J; Brown, Toby; Cordo, Vincent; Abraham, V. Mary; Alman MacDonagh, JD, Catherine; Sterling, John; et al.
No abstract available